PRECARIOUS EXISTENCE UNDER REPRESSION IN 1990s KOSOVO: A CASE STUDY OF AN ALBANIAN ARCHIVIST. - DUSHI, ARBNORA (Croatian Journal of Ethnology & Folklore Research / Narodna Umjetnost, 2026)
This study explores the precarious life of Albanians in Kosovo during the 1990s through the oral autobiographical narrative of a retired archivist at the Institute of Albanology in Prishtina. With four decades of institutional experience, the archivist offers a compelling personal narrative of cultural survival under systemic repression. The Institute, founded in 1953, became a target during the violent escalation of Serbian state control, culminating in the forced expulsion of its scientific staff in the early 1990s. This act not only displaced individuals, it also disrupted the scholarly continuity of one of Kosovo's key scientific and cultural institutions. The archivist's testimony captures this rupture while illuminating the broader landscape of institutional violence and state-sponsored erasure faced by Albanians in Kosovo. Her narrative highlights how intellectual communities responded by forming parallel academic structures sustaining scientific and cultural life. The study uses this oral history, an archive in itself, to interrogate the role of personal narrative in documenting institutional memory and reconstructing Kosovo's fraught historical landscape. By bringing her micro-narrative into dialogue with written sources, this work reflects on the violence, resilience, and fragility of life under occupation, while raising questions about memory, resistance, and the ongoing process of state-building in post-war Kosovo.